Performance of Local Government Apparatuses and Public Services: Survey on SKPD Kabupaten Bandung Barat Government - Darya Setia Nugraha; Teti Widia Komarawati (Indonesian Journal of Economics and Management, 2022)
One of the efforts made by the Government of Kabupaten Bandung Barat in avoiding the practice of KKN so that the goal of implementing good governance can be achieved is by implementing the government internal control system. In addition, the purpose of the government is to conduct public services that are effective and efficient, which can be seen from the commitment and performance of local government apparatus. This research aims to determine the effect of good governance, internal control system of Government and the organizational commitment to the public service through the performance of local government apparatus as an intervening variable. The type of research used is quantitative. The population in this research is the regional government working unit in the Kabupaten Bandung Barat government. The samples in this study were as much as 28 SKPD with a total of 208 respondents. Method of collecting data using questionnaires. Data analysis method using path analysis processed with IBM SPSS software version 26.0. Based on the results of the research, there is a positive and significant effect of good governance, government internal control system and organizational commitment to the performance of government apparatus both partially and simultaneously. The performance of local government apparatus has a positive and significant effect on public services. There is an indirect effect of good governance, government internal control system and organizational commitment to public service through the performance of local government apparatus as an intervening variable.